1999
DOI: 10.1002/(sici)1096-8628(19990730)85:3<243::aid-ajmg11>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

XLMR syndrome characterized by multiple respiratory infections, hypertelorism, severe CNS deterioration and early death localizes to distal Xq28

Abstract: We report on a family with severe X-linked mental retardation (XLMR) and progressive, severe central nervous system deterioration. Three of the five affected males died of secondary complications before the age of 10 years and none have survived past the age of 10. These complications included swallowing dysfunction and gastroesophageal reflux with secondary recurrent respiratory infections. In addition, hypotonia and a mild myopathy were also present. All had a characteristic facies, including downslanting pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 6 publications
1
55
0
1
Order By: Relevance
“…The genetically related Lubs syndrome (OMIM #300260) was first described in 1999, and etiologically resolved in 2005 as the MECP2 duplication syndrome. [4][5][6] Xq28 duplications of different sizes spanning the MECP2 gene have been identified to date as a common cause of mental retardation in males. In familial cases with X-linked pedigrees, the asymptomatic female carriers show a significant skewing of X-inactivation (XCI).…”
Section: Introductionmentioning
confidence: 99%
“…The genetically related Lubs syndrome (OMIM #300260) was first described in 1999, and etiologically resolved in 2005 as the MECP2 duplication syndrome. [4][5][6] Xq28 duplications of different sizes spanning the MECP2 gene have been identified to date as a common cause of mental retardation in males. In familial cases with X-linked pedigrees, the asymptomatic female carriers show a significant skewing of X-inactivation (XCI).…”
Section: Introductionmentioning
confidence: 99%
“…In our screen of a large cohort of patients with X-linked mental retardation (XLMR) by full coverage Xchromosome-specific array-CGH (Froyen et al 2007) and realtime quantitative PCR (qPCR), we identified small duplications at Xq28 in four unrelated male patients with severe to profound mental retardation and additional clinical features , referred to as the Lubs X-linked mental retardation syndrome (XLMRL; OMIM 300260) (http://www.ncbi.nlm.nih. gov/omim/) (Lubs et al 1999). Delineation of the minimal critical region and detection of a twofold increased expression of MECP2 mRNA in the patient-derived cell lines compared with controls pointed to an increased dosage of MECP2 as the cause of the MR phenotype, thereby demonstrating a new disease mechanism in mental retardation .…”
mentioning
confidence: 98%
“…The X-chromosome has become an obvious focus for mapping and identifying genes for syndromal and nonspecific mental retardation. Published XLMR studies have been reviewed, and of 178 XLMRrelated genes, 120 genes are associated with mental retardation (Lubs et al, 1999).…”
Section: Discussionmentioning
confidence: 99%